2023
DOI: 10.1097/md.0000000000033626
|View full text |Cite
|
Sign up to set email alerts
|

The ascendancy of research in acronyms related to COVID-19 displayed on a growth-share matrix (GSM): Bibliometric analysis

Abstract: Background: The acronym COVID, which stands for coronavirus disease, has become one of the most infamous acronyms in the world since 2020. An analysis of acronyms in health and medical journals has previously found that acronyms have become more common in titles and abstracts over time (e.g., DNA and human immunodeficiency virus are the most common acronyms). However, the trends in acronyms related to COVID remain unclear. It is necessary to verify whether the dramatic rise in COVIDrelated research can be obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…The TBG has been illustrated in bibliographical studies, [2,27,35] but no such IP points combined on the TBG, as we demonstrated in Figure 6. As such, the temporal visualization can be further improved when compared to the previous studies [30,36–50] using trend analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The TBG has been illustrated in bibliographical studies, [2,27,35] but no such IP points combined on the TBG, as we demonstrated in Figure 6. As such, the temporal visualization can be further improved when compared to the previous studies [30,36–50] using trend analysis.…”
Section: Discussionmentioning
confidence: 99%